OPTIMALISASI KONTRIBUSI PARIWISATA CEKING TERHADAP EKONOMI MASYARAKAT LOKAL - Adi Kampana, I Made (Jurnal Ilmiah Pariwisata; Volume 2 No.1 Hal 109-222 September 2012, 2012)
Based on the number of visitor to Ceking, it is known that only 3% which includes stay over night visitor, while the rest are one day visitors. These Conditions indicated tourism in Ceking have not optimally contribution to local economic communities due to the gap between actual and potential visitors spending. The gap is caused by leakage, which occurs by ineffectiveness and inadequate management of resources and market of tourism. In order to optimize economic contribution to the local community, some programs of tourism development in Ceking can be initiated. These programs include; cultural nuances of rural tourism development (village tourism), the development of rural night attractions, the development of core - plasma models between the hotel with a home stay, the utilization of local raw materials in the tourism products, the traditional transport development, potential market development and marketing partnership with a travel agent.
Keywords: optimization, contribution, economic, local community